2001
DOI: 10.1097/00007632-200111010-00023
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Insipidus Secondary to Penetrating Spinal Cord Trauma

Abstract: CDI is a complicated hormonal disorder characterized by excessive urine output. It is typically linked to an abnormality in the hypothalamohypophyseal axis that markedly reduces ADH production. The most common inciting causes are craniocerebral trauma, brain tumor and/or surgery, and central nervous system infection. Although uncommon, CDI should be considered when a spinal trauma patient develops excessive urine output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…Several studies have reported that patients undergoing spine surgery or spinal cord trauma patients developed excessive urine output [16]. Second, it has been reported that calcium channel antagonists enhance the diuretic activity of dexmedetomidine in rats by directly inhibiting renal tubular water and electrolyte reabsorption and blocking the inhibitory actions of angiotensin and vasopressin on renin secretion [15]. In the present case, the patient had taken a calcium channel antagonist (felodipine) for hypertension.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Several studies have reported that patients undergoing spine surgery or spinal cord trauma patients developed excessive urine output [16]. Second, it has been reported that calcium channel antagonists enhance the diuretic activity of dexmedetomidine in rats by directly inhibiting renal tubular water and electrolyte reabsorption and blocking the inhibitory actions of angiotensin and vasopressin on renin secretion [15]. In the present case, the patient had taken a calcium channel antagonist (felodipine) for hypertension.…”
Section: Discussionmentioning
confidence: 63%
“…grav. U urine specific gravity, Osm U urine osmolality (mOsm/kg H 2 O), Osm P plasma osmolality (mOsm/kg H 2 O), BUN blood urea nitrogen, Cr blood creatinine, BP arterial blood pressure (mmHg), HR heart rate (beats/min), CO cardiac output, SVV stroke volume variation, EBL estimated blood loss (ml), UOP urine output (ml), AR Ringer's acetate solution, NS normal saline, HES hydroxyethyl starch, PRBC packed blood red cells, FFP fresh frozen plasma, D5W 5 % dextrose solution, NR not recorded, POD postoperative day effect and a dose-dependent increase in the frequency of voiding [15]. Although dexmedetomidine-induced polyuria and hypernatremia may be explained by the previously stated mechanisms, studies in human are still sparse.…”
Section: Discussionmentioning
confidence: 99%
“…42,43 An interesting particularity noticed in one of our subjects was the triple association between AS-SCI and a transient diabetes insipidus.…”
Section: Discussionmentioning
confidence: 73%
“…4,5 It has been hypothesized that CDI can be caused by spinal injury if there is hypoperfusion and hypoxia of the neurohypophysis and median eminence as a result of vasomotor instability. 6 Farelli and Staas 2 described a quadriplegic patient with partial CDI, which is a mild form of the disease, diagnosed after the spinal trauma because the patient could not spontaneously empty his bladder. An intermittent catheterization program was unmanageable due to his production of a copious amount of urine.…”
Section: Discussionmentioning
confidence: 99%